Mosque as a Place To Build Moderate Community - Cucu Cucu; Hesty Nur Rahmi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
This study was to investigate the influence of mosques in developing moderate communities in West Kalimantan. Mosques are Da'wah institutions that are aligned with the community's values. Aside from serving as a place of prayer, the mosque is also a source of empowerment for women. Threrefore, the focus of this article is on the role of mosques in the development of Islam and the adoption of models of religious moderation in mosques. This study used a sociological approach. This study reveals that, despite the fact that a certain group was responsible for the mosque's construction, the mosque's management does not take sectarianism into consideration. A significant indication that mosques play a vital role in the development of moderate Islam is their refusal to join sides with particular parties. The mosque serves as a social institution in addition to serving as a place of prayer. The successful implementation of modern mosque administration principles is a model that may be adopted by a number of other mosques to enhance their facilities as a location to foster the development of a moderate community. When modern management ideas are used to mosque management operations, the realization of the mosque's existence is possible to achieve